The Comparison of Aggression between Professional and Semi-Professional Male Taekwondo Athletes in Isfahan, Iran - Mojtaba Salemi Khozani; Kaveh Khabiri Khabiri; Bahram Ghadimi; Sepideh Mehraein; Aida Mehrad (Journal of Educational, Health and Community Psychology, 2017)
AbstractAggression is one of the general phenomenon that athletes often directly or indirectly deal with. There are rare issues that are significant as much aggression and violence in sport. The explanation for violent behavior in humans is often the subject of research in the science of sociology. Social changes around the world in recent centuries had a significant impact on cultural structure. In this study, the researchers focused on the aggression of professional and semi-professional athletes in Taekwondo in Isfahan, Iran. The cross-sectional method was applied in this study. To analyze, we examined the relationships between predictor variables and the dependent variable or the variance criterion to explain the changes. The results shown that there was no significant difference between terms of anger and physical aggression among professional and semi-professional. On the other hand, there was meaningful differences between verbal aggression and hostility amongst participants. In addition, the amounts of aggression amongst professional players were more than semi-professional players.Â Keywords: Aggressive, Athlete, Iran, Isfahan, Professional, Semi-professional, Taekwondo